Climate policy and optimal public debt - Maximilian Kellner; Marco Runkel (International Tax and Public Finance, 2023)
Employing a two-period model with an environmental externality, this paper investigates the relation between emission taxation and the optimal level of public debt. The central insight is that the effect of emission taxation on optimal borrowing is ambiguous and may lead to lower or higher optimal debt. In the context of climate change, we even show that the counterintuitive result of a higher optimal debt level is likely in the short-run and possibly also in the long-run, a result that provides a novel rationale for public borrowing. Our basic arguments turn out to be robust against several generalization.
Keywords: H23; H63; Q54; Q58; 340; Adaptation; Environmental externality; Public debt; Climate policy; Tax smoothing